The value of \(tan^{-1}(1)\) + \(cos^{-1}({-1\over 2})\) + \(sin^{-1}({-1\over 2})\) is equal to

Solution :

We have, \(tan^{-1}(1)\) + \(cos^{-1}({-1\over 2})\) + \(sin^{-1}({-1\over 2})\)

= \(\pi\over 4\) + \(2\pi\over 3\) – \(\pi\over 6\) = \(3\pi\over 4\)


Similar Questions

Solve the equation : 2\(tan^{-1}({2x+1})\) = \(cos^{-1}x\)

Prove that : \(sin^{-1}{12\over 13}\) + \(cot^{-1}{4\over 3}\) + \(tan^{-1}{63\over 16}\) = \(\pi\)

Evaluate \(sin^{-1}(sin10)\)

Prove that : \(cos^{-1}{12\over 13}\) + \(sin^{-1}{3\over 5}\) = \(sin^{-1}{56\over 65}\)

Find the value of \(sin^{-1}({-\sqrt{3}\over 2})\) + \(cos^{-1}(cos({7\pi\over 6}))\).

Leave a Comment

Your email address will not be published.